Water Distribution Systems Analysis 2010 2011
DOI: 10.1061/41203(425)62
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simultation of Arsenate Fate and Transport in a Distribution System Simulator

Abstract: Multi-species water quality models can be used to predict the fate and transport of contaminants such as arsenic in water distribution networks. In recent work, water quality models have been used to simulate hypothetical contamination events, estimate potential human health effects, and characterize the ability of sensors to detect contamination. Little work has been done to calibrate water quality models and validate them against experimental data generated in Distribution System Simulators (DSSs). In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…The physics is described by the Langmuir adsorption model tD+vxD=1rhf(D,A),tA=f(D,A) with f(D,A)=11k1+1kf(SmaxA)(D(SmaxA)KeqA), where D is the concentration of dissolved arsenate and A the concentration of arsenate adsorbed at the pipe wall. We adopt realistic parameter values from v=100emm/min,rh=500.3eml/m2,k1=0.20eml/(mg0.3emmin),Smax=1000.3emmg/m2,Keq=0.05370emmg/l,kf=2.40.3eml/(m20.3emmin), and consider the system on the approximately positively invariant Ω given by D ∈[0,1]mg/l and A ∈[0,100]mg/m 2 . To discretize time and space, we decouple the advection and the reaction step with the Trotter formula .…”
Section: Application: Inference Of Arsenate Sourcementioning
confidence: 99%
“…The physics is described by the Langmuir adsorption model tD+vxD=1rhf(D,A),tA=f(D,A) with f(D,A)=11k1+1kf(SmaxA)(D(SmaxA)KeqA), where D is the concentration of dissolved arsenate and A the concentration of arsenate adsorbed at the pipe wall. We adopt realistic parameter values from v=100emm/min,rh=500.3eml/m2,k1=0.20eml/(mg0.3emmin),Smax=1000.3emmg/m2,Keq=0.05370emmg/l,kf=2.40.3eml/(m20.3emmin), and consider the system on the approximately positively invariant Ω given by D ∈[0,1]mg/l and A ∈[0,100]mg/m 2 . To discretize time and space, we decouple the advection and the reaction step with the Trotter formula .…”
Section: Application: Inference Of Arsenate Sourcementioning
confidence: 99%
“…[6][7][8][9][10]. In this case the bulk live heterotrophic bacteria were chosen to represent the biocontaminant.…”
Section: Simulation Experimentsmentioning
confidence: 99%
“…We adopt realistic parameter values from [26,37], whereas in Figure 6(d) the pattern size is extended by W = {−1, 0} to V = {−1, 0}. It is observed that in this example increasing the pattern size does not improve the result if compared to the Monte Carlo case, but increasing the state space resolution has a notable effect.…”
Section: Arsenate Fate In Water Pipementioning
confidence: 99%
“…Consider the advection and adsorption of arsenate in drinking water pipes, a topic that has attracted a lot of attention in the water supply community lately [39,26]. We describe a water tank on a hill and a pipe to a consumer in a valley.…”
Section: Arsenate Fate In Water Pipementioning
confidence: 99%